Comparison of the Contents Pancasila Education and Citizenship From 1975-2013 Curriculum in Indonesian at The 21st Century - Gunawan Santoso; Mamun Murod (NAROTAMA UNIVERSITY, Indonesia, 2021)
Abstract The study are philosophically Citizenship Education curricular subjects and is a learning tool creates learners who have mental Pancasilaist in word, deed and behavior in everyday life. Civics is the best material is original from Indonesia is not copied from other countries, including the Pancasila, the 1945 Constitution, the Republic of Indonesia, national unity, and the Red and White. The findings of this study also have implications for the development of scientific development theory and Citizenship Education in terms of the future of Indonesian high school curriculum. This research uses the method of literature analysis with grounded theory is a qualitative research method that uses a number of systematic procedures to develop a theory compiled inductive. Research grounded theory, this research inductive research techniques, emphasizes observation and develops a base of